Exploring Ethical Implications of Ai in Modern Society - Neha Madhava Sundhram; J. P. Pramod (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study aims to analyze the ethical and societal implications of artificial intelligence (AI) across various dimensions and emphasize the importance of responsible AI development and deployment. There is a possibility that artificial intelligence will have positive effects, such as increased productivity and reduced human bias; however, there are also potential negative effects associated with it. In addition to this, it explores how legal practitioners might learn to maximise the use of AI tools while maintaining their authoritative decision-making positions without having to give up their positions. The study is grounded in the framework of responsible AI development and deployment, which seeks to minimize risks and optimize benefits for society. The research identifies significant ethical and societal implications of AI, highlighting the importance of addressing privacy, bias, transparency, and accountability concerns. The research employs critical analysis and examines case studies to assess ethical considerations in AI development, societal impacts in employment, healthcare, education, and social equality, and concerns regarding privacy, bias, transparency, and accountability. It also stresses the need for responsible AI development and deployment in mitigating risks and maximizing benefits across various sectors.